The Proudest Blue : A Story of Hijab and Family - Muhammad, Ibtihaj, 1985-; Ali, S. K.; Aly, Hatem (New York ; Little, Brown and Company, 2019)
Faizah relates how she feels on the first day her sister, sixth-grader Asiya, wears a hijab to school.
Keywords: Hijab (Islamic clothing) -- Juvenile fiction; Sisters -- Juvenile fiction; First day of school -- Juvenile fiction; Schools -- Juvenile fiction; Muslims -- Juvenile fiction; Islam -- Juvenile fiction. -- Customs and practices; Hijab (Islamic clothing) -- Fiction; Sisters -- Fiction; First day of school -- Fiction; Schools -- Fiction; Muslims -- Fiction; Islam -- Fiction. -- Customs and practices; Picture books